Caracterização de compostos bioativos em uva da cultivar Isabel precoce (Vitis labrusca L.) durante o desenvolvimento fisiológico, cultivada no cerrado goiano - Pádua, Dalila Rayane de Lima (2018)
The grape stands out among fruits and vegetables as one of the largest sources of phenolic compounds. Thus, the objective of this work was to evaluate the content of biocomposites in the early Isabel cultivar during physiological development. The cycle comprised a 90 days after anthesis (DAA). There was a decrease in acidity, increase in pH and soluble solids, and change in fruit staining with significant variations at 60 DAA. The content of phenolic compounds presented higher contents for seeds during maturation (60-90 DAA) followed by berry, skin and pulp. The seeds presented better antioxidant activity during all maturation times, by the DPPH and Phosphomolybdenum methods, and ABTS at 60 DAA. The berries presented better antioxidant activity at 10 DAA for the three evaluated methods (DPPH, ABTS and Phosphomolybdenum). In the skin, the antioxidant activity by the ABTS assay presented higher levels from 70 DAA. The pulp was the tissue that presented lower contents of total phenolic compounds and antioxidant activity in comparison with the others. Of the individual phenolic compounds, three chlorogenic acids were present in the berries (10 to 50 DAA), peels and pulps (60 to 90 DAA), and catechin and epicatechin in the seeds (60 to 90 DAA), all of which presented significant reduction throughout development of the fruit.